Yeast hormone response element assays detect and characterize GRIP1 coactivator-dependent activation of transcription by thyroid and retinoid nuclear receptors - Walfish, Paul G. (The National Academy of Sciences of the USA, 1997)
The mouse glucocorticoid receptor-interacting protein (GRIP1) is a member of the ERAP160 family of nuclear receptor (NR) coactivators (including SRC-1 and TIF2) which function as bridging proteins between ligand-activated NRs bound to cognate hormone-response elements (HREs) and the transcription initiation apparatus (TIA). Although these coactivators bind to several NRs, studies overexpressing these coactivators with these NRs in mammalian cells have not uniformly observed a corresponding enhancement of ligand-dependent transactivation. Here, we show that GRIP1 interacts in vitro in a ligand-dependent manner with thyroid receptor, retinoic acid receptor, and retinoid X receptor. Additionally, in yeast (Saccharomyces cerevisiae) GRIP1 coactivator protein markedly increased the ability of these full-length class II NRs to transactivate β-galactosidase reporter genes containing cognate HREs. The magnitude of GRIP1 enhancement of liganded NR homodimer was dependent upon NR subtype and HRE configuration. For most HRE configurations, thyroid receptor and retinoic acid receptor homodimers were essentially unresponsive or very weakly active in the absence of GRIP1, but GRIP1 dramatically restored the ligand-dependent function of these NRs. Although GRIP1 exerted no significant effect on NR homodimers in the absence of their cognate ligands, it increased the transactivation of unliganded NR heterodimers. Whether GRIP1 increased ligand-dependent transactivation of a heterodimer to levels greater than that of the cognate homodimer was determined by HRE configuration and copy number. Compared with the limitations of yeast two-hybrid and mammalian coexpression systems, the yeast HRE-assay systems described in this report facilitated both the detection of putative mammalian NR coactivator function and the elucidation of their mechanisms of transactivational enhancement.